Current Trends in Outpatient Spine Surgery. Issue 9 (November 2016) - Ahn, Junyoung; Bohl, Daniel D.; Tabaraee, Ehsan; Basques, Bryce A.; Singh, Kern
Abstract : Because of the increasing pressure to contain health-care–related costs, the number of spinal surgeries performed in the outpatient setting has significantly increased. The higher perioperative efficiency and greater predictability of associated costs offer significant incentives for payers and providers to move surgical procedures into the outpatient setting. Nonetheless, judicious patient selection is advised to optimize outcomes.